2006
DOI: 10.1094/mpmi-19-0789
|View full text |Cite
|
Sign up to set email alerts
|

The Arabidopsis thaliana JASMONATE INSENSITIVE 1 Gene Is Required for Suppression of Salicylic Acid-Dependent Defenses During Infection by Pseudomonas syringae

Abstract: Many plant pathogens suppress antimicrobial defenses using virulence factors that modulate endogenous host defenses. The Pseudomonas syringae phytotoxin coronatine (COR) is believed to promote virulence by acting as a jasmonate analog, because COR-insensitive 1 (coil) Arabidopsis thaliana and tomato mutants are impaired in jasmonate signaling and exhibit reduced susceptibility to P. syringae. To further investigate the role of jasmonate signaling in disease development, we analyzed several jasmonate-insensitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
144
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 223 publications
(154 citation statements)
references
References 72 publications
8
144
0
2
Order By: Relevance
“…Contrary to insects that activate the JA pathway and trigger a strong defense response, this bacterial pathogen activates the JA pathway to promote susceptibility (Feys et al, 1994;Kloek et al, 2001;Laurie-Berry et al, 2006). Consistent with previous reports, the JA-insensitive mutants coi1-1 and myc2 showed increased resistance (both in terms of bacterial growth and leaf symptoms) that correlated with their levels of JA insensitivity ( Figures 10A and 10B).…”
Section: Analysis Of Ja-dependent Defense Responsessupporting
confidence: 89%
“…Contrary to insects that activate the JA pathway and trigger a strong defense response, this bacterial pathogen activates the JA pathway to promote susceptibility (Feys et al, 1994;Kloek et al, 2001;Laurie-Berry et al, 2006). Consistent with previous reports, the JA-insensitive mutants coi1-1 and myc2 showed increased resistance (both in terms of bacterial growth and leaf symptoms) that correlated with their levels of JA insensitivity ( Figures 10A and 10B).…”
Section: Analysis Of Ja-dependent Defense Responsessupporting
confidence: 89%
“…Next, we examined the response of ber6 plants to infection by Pseudomonas syringae pv tomato (Pst) DC3000. As measured by leaf symptoms ( Figure 1F) and pathogen growth ( Figure 1G) of the infected plants, the effects of Pst DC3000 infection in ber6 are largely similar to those in the coi1-2 mutant, which harbors a point mutation of the JA receptor gene COI1 and therefore is resistant to Pst DC3000 (Kloek et al, 2001;Xu et al, 2002;Laurie-Berry et al, 2006). Together, our results support that ber6 is a JA signaling mutant that is defective in JA-induced defense gene expression.…”
Section: Resultssupporting
confidence: 67%
“…Contrary to necrotrophic pathogens, which activate the JA pathway and trigger a strong defense response, Pst produces a JA-mimicking phytotoxin, coronatine (COR), which can induce a set of JA-responsive genes to promote susceptibility (Laurie-Berry et al, 2006). As expected, we found that Pst induced RGL3 expression in leaves 3 d after inoculation (Figures 7A and 7B).…”
Section: Rgl3 Modulates Ja-dependent Plant Defense Responsessupporting
confidence: 72%